Kualitas Pelayanan Publik di Desa Potanga Kecamatan Boliyohuto Kabupaten Gorontalo - Widya Kurniati Mohi; Irmanovika Mahmud (Publik : (Jurnal Ilmu Administrasi), 2017)
Abstract This research used a qualitative method through natulastic approach as the part of the government research, with the aim to determine the public services quality also obstacles in improving of public services effort quality in village of Potanga sub-district of Boliyohuto. Source of research data enable two data sources are sources of primary data and source secondary data. Based on the research result can be described; (1) Effort to improve public services in village of Potanga can be identified as follow; a) to improve the principle of public services; b) the principle of public services; and c) to improve public service standarts. (2) Efforts to improve the public services in village of Potanga can be caterogized as good and in accordance with the public service policies, laws, public service, and the role, duties and responsibilities of the village government to the public service. (3) Obstackle in improving of the public services effort quality in villafe of Potanga, that is internal resistance in the form of problem officer/staff both the term of quantity nor in term of the quality of human resources. (4) External obstacles sourced from the society reason of physical and phycological and environmental. Penelitian ini menggunakan metode kualitatif melalui pendekatan naturalistik sebagai bagaian dari penelitian pemerintahan, dengan tujuan untuk mengetahui kualitas pelayanan publik serta hambatan dalam upaya peningkatan kualitas pelayanan publik didesa Potanga Kecmatan Boliyohuto. Sumber data penelitian memfungsikan dua sumber data yaitu sumber data primer dan sumber data sekunder Berdasarkan hasil penelitian dapat diuraikan; (1) Upaya peningkatan pelayanan publik didesa Potanga dapat diidentifikasi sebagai berikut; a) peningkatan azas layanan publik; b) prinsip layanan publik; dan c) peningkatan standar layanan publik. (2) Upaya peningkatan pelayanan publik didesa Potanga dapat dikategorikan baik dan telah sesuai dengan kebijakan pelayanan publik, undang-undang pelayanan publik, serta peran, tugas dan tanggung jawab pemerintah desa terhadap pelayanan publik. (3) Hambatan upaya-upaya peningkatan kualitas pelayanan publik di desa Potanga, yaitu hambatan internal berupa masalah aparat/staf baik dari segi kuantitas maupun dalam hal kualitas sumber daya manusia (4) Hambatan eksternal bersumber dari masyarakat karena alasan fisik dan psikis dan lingkungan